2009
DOI: 10.1093/eurheartj/ehp220
|View full text |Cite
|
Sign up to set email alerts
|

Long-term myocardial functional improvement after autologous bone marrow mononuclear cells transplantation in patients with ST-segment elevation myocardial infarction: 4 years follow-up

Abstract: AimsTo evaluate the safety profile and efficacy of bone marrow mononuclear cells (BMMNC) transplantation for ST-segment elevation myocardial infarction (STEMI) by assessing patients and their left ventricular function at up to 4 years follow-up.Methods and resultsEighty-six patients with STEMI who had successfully undergone percutaneous coronary intervention (PCI) were randomized to receive intracoronary injection of BMMNC (n = 41) or saline (n = 45). Left ventricular ejection fraction, as evaluated by UCG, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(77 citation statements)
references
References 37 publications
1
74
1
1
Order By: Relevance
“…32 Subgroup analysis based on the study by Cao also suggested that younger patients might benefit more from BMC infusion than older patients. 19 In the second instance,more significant LVEF improvementwas observed when BMC were administered 6 or 7 days after acute MI compared to 5 days after acute MI. A more favorable niche of transplanted BMC at 6 or 7 days following acute MI, may contribute to the superior effects of BMC transferred during this time window.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…32 Subgroup analysis based on the study by Cao also suggested that younger patients might benefit more from BMC infusion than older patients. 19 In the second instance,more significant LVEF improvementwas observed when BMC were administered 6 or 7 days after acute MI compared to 5 days after acute MI. A more favorable niche of transplanted BMC at 6 or 7 days following acute MI, may contribute to the superior effects of BMC transferred during this time window.…”
Section: Discussionmentioning
confidence: 86%
“…19 A sensitivity analysis with or without this study showed that BMC transfer was still associated with significant effects on LVEF and LVESV and was associated with a trend toward significant effect on LVEDV and infarct size. This systematic review was based on a comprehensive search strategy.…”
Section: Sensitivity Analysis and Publication Bias Assessmentmentioning
confidence: 82%
“…Of these, 622 were nonrandomized studies, editorials, or reviews, and 83 of these were examined in more detail. Seventeen of the 83 references were eligible for inclusion [2][3][4][5][6][7][19][20][21][22][23][24][25][26][27][28][29] (Figure 1). …”
Section: Search Resultsmentioning
confidence: 99%
“…Nine of 17 trials implemented identical cardiac catheterization injection procedures after bone marrow aspiration in both the BMSC and control groups to maintain study blindness [2][3][4][5][6][7]19,21]. The surgeon was unaware whether cells or only saline was being injected.…”
Section: Discussionmentioning
confidence: 99%
“…Strauer's group, in their non-randomized, but well controlled study had showed that the benefit on intracoronary bone marrow derived MNC infusion after infarction for the myocardial performance sustained after 5 years and that even decreased the abnormal heart rate variability, late potentials and ectopic beats (Yousef (Cao et al, 2009), also indicated the persistent improvement of LVEF (over 4 years) in AMI patients treated with intracoronary bone marrow MNC compared to controls, but interestingly without significant improvement on viability. In BOOST trial (Meyer et al, 2009) patients with more transmural extension of infarction appeared to benefit from BMC transfer throughout the five years.…”
Section: Important Clinical Trials On Stem Cell Therapy In Acute Myocmentioning
confidence: 99%